Ecologia e comportamento de Callicebus bernhardi em um fragmento florestal em Rondônia, Brasil - Lopes, Karine Galisteo Diemer (2016)
Titi monkeys (Callicebus) are well-known for their secondary and anthropogenic forest environments. However, there is scanty information on the ecology and behavior of most species. This study reports the results of the first study on the ecology and behavior of the Prince Bernhard’s titi monkey (Callicebus bernhardi). A group composed of four individuals (an adult male, an adult female, a young male, and a young female) inhabiting a forest fragment of 2.3 ha in Rolim de Moura, Rondônia, Brazil, was followed for thirteen 7-day sampling periods (total=90 days and 1,010 hours of observation) from March to September 2015. The study covered both the rainy (March-May and September) and the dry (June-August) season. The behavior was recorded by the instantaneous scan sampling method, resulting in 20,023 records. Food availability was estimated based on an overall floristic survey together with data from phenologic and invertebrate surveys conducted every two weeks immediately before each behavioral sampling period. Resting was the most frequent behavior (45.2%), followed by moving (28.5%), feeding (17.4%), and social behaviors (7.5%). The diet was predominantly frugivorous (78% of feeding records), supplemented with flowers (6%), leaves (5.9%), invertebrates (4.5%) and seeds (1%). The activity budget and diet composition varied during the study. The behavior of titi monkeys during resting was consistent with a behavioral thermoregulation strategy. Sitting was the primary resting posture (62%), but the titis increased the use of heat dissipating postures with increasing air temperature. Additionally, air temperature influenced microhabitat selection, affecting the animals’ height in the canopy and their exposure to sunshine. We conclude that C. bernhardi inhabiting a small forest fragment shows an activity budget and diet similar to other titi monkey species and uses behavioral thermoregulation strategies to avoid body overheating similar to those recorded for other primates experiencing high ambient temperature.